Between Minangkabau Customary and Islamic Law: Adoption of Children Born Out of Wedlock - Esiesti Ega Wahyuni; Beni Firdaus (Yayasan Lembaga Studi Makwa, 2026)
This study aims to examine the adoption of children born out of wedlock within the interaction between Minangkabau customary and Islamic law, focusing on legal protection, social acceptance, and the child’s best interests. It also evaluates the compatibility of adoption practices with the objectives of Maqasid Shariah. This research employs an empirical juridical approach using qualitative methods. Data were collected through interviews with customary leaders, religious scholars, adoptive families, and local officials in West Sumatra, supported by observations and document analysis of customary norms, legislation, and Islamic legal sources. The findings reveal that Minangkabau customary law generally accepts the adoption of children born out of wedlock as a means of providing care, family support, and social integration without changing biological lineage. Likewise, Islamic law permits adoption provided that nasab, inheritance rights, and legal identity remain unchanged. Although the legal consequences differ, both legal systems prioritize child welfare and social responsibility. Analysis based on Maqasid Shariah demonstrates that adoption promotes the protection of life, lineage, and property while strengthening family solidarity and social justice. The study concludes that adopting children born out of wedlock can serve as an effective child protection mechanism when implemented consistently with customary and Islamic legal principles. Academically, this research contributes an integrated socio-legal framework combining Minangkabau customary law and Maqasid Shariah, enriching discussions on legal pluralism, child adoption, and child protection while providing a valuable reference for future legal reform, judicial interpretation, and policymaking in Indonesia.